Imágenes literarias para el legado político de Alejandro. Comentario estilístico de Mor. 336E-337A - Pérez-Jiménez, Aurelio (My University, 2015)
In this paper I tray to underline the originality of Plutarch through the litterary construction of two images concerning the figure of Alexander. One of them, which compares the situation of Macedonia after his death with the blind Ciclope, has been provided by the colections of sayings and anecdotes to him, but litterary enriched by the Chaeronean; the other, equaling the political action of Alexander's sucessors to the members of the body when it has been left by the soul, seems to be a creation of Plutarch himself.
Keywords: Plutarco - Crítica e interpretación; Plutarco; Plutarco. Estilo